Financial Literacy, Microfinance, and Women Empowerment: Pathways to Sustainable Development in Haiti and Burundi - Jean-Baptiste Innocent Nyangoma, Jean-Baptiste Innocent Nyangoma; Marie-Lourdes Joseph; Frantz Jacques Louis; Amina Njeri Kamau (Yayasan Amerta Insan Unggul, 2024)
This study examines the interrelationships between financial literacy, microfinance access, and women’s empowerment as pathways to sustainable development in two fragile-state contexts—Haiti and Burundi. Using a mixed-method comparative design, data were collected from 768 women micro-entrepreneurs through structured surveys and ten qualitative interviews with microfinance practitioners. Quantitative analysis employing multiple regression and PLS-SEM revealed that both financial literacy (β = 0.421, p < 0.001) and microfinance services (β = 0.387, p < 0.001) significantly and positively influence women’s empowerment. Moreover, empowerment mediates the relationship between financial inclusion variables and sustainable development outcomes (β = 0.463, p < 0.001). Comparative findings indicate that literacy-driven empowerment is more prominent in Haiti, where digital finance and remittances dominate, while access-driven empowerment prevails in Burundi’s agrarian context. The integrated effects suggest that literacy amplifies the benefits of microfinance by enhancing women’s financial decision-making, confidence, and control over resources. The study contributes to empowerment theory by empirically validating the synergistic interaction between knowledge and financial access and offers policy insights emphasizing gender-sensitive financial education, digital microfinance expansion, and regulatory inclusion. These results highlight that fostering both financial capability and access is essential for advancing Sustainable Development Goals (SDGs 5, 8, and 10) in fragile economies, where empowering women serves as both a developmental strategy and a catalyst for inclusive and resilient growth.